2016
DOI: 10.1016/j.jneb.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nutrition Literacy of Parents and Its Relationship With Child Diet Quality

Abstract: Objective To estimate the reliability and validity of the Nutrition Literacy Assessment Instrument for Parents (NLit-P) and to investigate relationships between parental nutrition literacy, parental and child BMI, and child diet quality (Healthy Eating Index, HEI). Methods Cross-sectional study of 101 parent-child dyads which collected measures of socioeconomic status, nutrition literacy, 2–24 hour child diet recalls, and BMI. Reliability of NLit-P was assessed by confirmatory factor analysis. Pearson correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 29 publications
5
64
1
4
Order By: Relevance
“…The role of some antecedents and consequences discussed in the text was demonstrated by primary studies [25,[42][43][44][45]. The role of some antecedents and consequences discussed in the text was demonstrated by primary studies [25,[42][43][44][45]].…”
Section: Antecedents Of Nl and Flmentioning
confidence: 97%
See 1 more Smart Citation
“…The role of some antecedents and consequences discussed in the text was demonstrated by primary studies [25,[42][43][44][45]. The role of some antecedents and consequences discussed in the text was demonstrated by primary studies [25,[42][43][44][45]].…”
Section: Antecedents Of Nl and Flmentioning
confidence: 97%
“…Considering the youngest subjects, the role of the expert in imparting adequate knowledge and practices is taken over by parents. The role of parents can be considered as an antecedent of NL [28,43,48], and the results obtained by Gibbs et al [43] indicated a significant positive relationship between parents' level of NL and children's diet quality.…”
Section: Antecedents Of Nlmentioning
confidence: 99%
“…But it is noteworthy that behind the dietary behavior and intake, the individual knowledge, skills and behaviors required to plan, manage, select, prepare and eat foods, which is de ned as FNL, may play an important role [1; 27]. A cross-sectional study of 101 parent-child dyads showed that for every 1% increase in Nutrition Literacy Assessment Instrument for Parents (NLit-P), there was a 0.51 increase in child diet quality (Healthy Eating Index) [11].Till now few studies focused on the effect of FFE on . Our results furtherly showed the children with higher level of caregiver's FNL were less likely to be overweight or obesity (OR = 0.043, 95%CI: 0.292-0.981, P < 0.05).…”
Section: Multivariable Analysismentioning
confidence: 99%
“…Heather D. Gibbs, et al, 6 dalam penelitiannya terkait literasi gizi pada orang tua dan hubungannya dengan kualitas diet anak menyimpulkan bahwa literasi gizi pada orang tua merupakan suatu pendidikan yang penting untuk dilaksanakan karena akan menentukan sejauh mana kualitas diet anak-anaknya. Penelitian ini mengungkapkan bahwa kualitas diet pada anak dikaitkan dengan pendapatan orang tua, usia, dan tingkat pendidikan (Pvalue <0,001) dan hasil analisis multivariat menunjukkan bahwa untuk setiap 1% peningkatan literasi gizi, ada peningkatan child Healthy Eating Index atau indeks makan sehat sebesar 0,51 (koefisien multivariat, 0,174; Pvalue <0,001).…”
Section: Pendahuluanunclassified